Slow-water-absorption hydrogel for simulating nerve compression model and preparation method of slow-water-absorption hydrogel

Through chemical crosslinking and electrostatic physical crosslinking, an interpenetrating network composite hydrogel was prepared, which solved the problem of excessively fast water absorption rate of hydrogels and difficult to balance the compression performance and slow water absorption performance in the prior art, and achieved a balance between slow water absorption and excellent compression performance of hydrogels.

CN119798710AActive Publication Date: 2025-04-11JIANGNAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411789017.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-11
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

In the prior art, hydrogels that simulate nerve compression have a very fast water absorption rate due to the dense network structure, and the compression performance and slow water absorption performance are difficult to balance, making it impossible to accurately simulate the chronic compression of the nerve.

Method used

Interpenetrating network composite hydrogels are prepared by chemical crosslinking and electrostatic physical crosslinking. The specific method includes preparing a specific concentration of chitosan hydrochloride aqueous solution, adding acrylamide and sodium alginate solutions, adding photoinitiator and crosslinking agent, and finally forming a SA-PAM-CSCL hydrogel under ultraviolet light irradiation.

Benefits of technology

The balance between the slow water absorption and compression properties of the hydrogel is achieved. The swelling equilibrium time is not less than 90h, the equilibrium swelling rate is not less than 300%, the compressive strength and compression modulus are not less than 20MPa, and the five compression cycle curves are basically overlapped.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798710A_ABST
    Figure CN119798710A_ABST
Patent Text Reader

Abstract

The invention discloses slow-water-absorption hydrogel for simulating a nerve compression model and a preparation method of the slow-water-absorption hydrogel, and belongs to the technical field of high polymer materials. The SA-PAM-CSCL composite hydrogel is prepared by adopting an ultraviolet light irradiation method, a monomer AM and a cross-linking agent are subjected to free radical polymerization under the action of a photoinitiator to prepare a PAM network, a basic hydrogel skeleton is obtained,-NH2 in PAM macromolecules and-COOH in SA molecules are subjected to chemical cross-linking to form amido bonds, SA and CSCL are subjected to mutual electrostatic interaction, and thus the hydrogel is prepared. An interpenetrating network structure among macromolecules is formed. Cyclic compression curves of the composite hydrogel are almost overlapped, so that the composite hydrogel shows good elastic property and has very excellent self-recovery performance; meanwhile, all the used raw materials have good biocompatibility, and the material is an ideal material for constructing a simulated nerve compression model.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a slowly water-absorbing hydrogel for simulating a nerve compression model and a preparation method thereof. Background Art

[0002] Hydrogel is a polymer material with a three-dimensional network structure formed by chemical crosslinking (through covalent bonds, etc.) or physical crosslinking (such as physical crystallization, coordination bonds, and hydrogen bonds, etc.) of a single or multiple homopolymers or copolymers. It has both hydrophilic and hydrophobic properties and can absorb water and swell in an aqueous medium to retain most of the water but will not dissolve. Among them, slow water-absorbing hydrogels can be used to simulate nerve compression models because of their slow water absorption, strong compressibility, and good biocompatibility.

[0003] Polyacrylamide (PAM) is a general term for polymers obtained by copolymerization of acrylamide homopolymers or other monomers. It is one of the most widely used varieties of water-soluble polymers. However, due to its single network structure, pure PAM hydrogel has a very fast water absorption rate and poor compression performance, making it difficult to use in simulating nerve compression models. Therefore, it is necessary to add other monomers to form an interpenetrating network to achieve slow water absorption and strong compressibility, which can be used to accurately simulate chronic nerve compression.

[0004] Existing technology has found that hydrogels that simulate nerve compression have good compression properties due to their dense network structure, but their water absorption rate is very fast and the equilibrium swelling time is very short. Therefore, there is an urgent need to develop a hydrogel that balances compression properties and slow water absorption properties. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a slowly water-absorbing hydrogel for simulating a nerve compression model.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions, including:

[0009] Chitosan hydrochloride (CSCL) and deionized water were mixed to obtain solution A;

[0010] Acrylamide and sodium alginate are mixed evenly with deionized water to obtain solution B;

[0011] Add photoinitiator and crosslinking agent into solution B and mix evenly to obtain solution C;

[0012] Solution C and solution A were stirred into a uniform solution to obtain a SA-PAM-CSCL gel solution, which was then irradiated with 365 nm ultraviolet light to obtain a SA-PAM-CSCL hydrogel.

[0013] As a preferred solution of the method for preparing the slowly water-absorbing hydrogel for simulating a nerve compression model of the present invention, the mass fraction of chitosan hydrochloride in the solution A is 4.8-5.2%.

[0014] As a preferred embodiment of the method for preparing the slowly water-absorbing hydrogel for simulating a nerve compression model of the present invention, the mass fraction of acrylamide in the solution B is 12.0-12.5%, and the mass fraction of sodium alginate is 1.8-2%.

[0015] As a preferred embodiment of the method for preparing the slowly water-absorbing hydrogel for simulating a nerve compression model of the present invention, in the solution C, the mass fraction of the photoinitiator is 0.7-0.8%, and the mass fraction of the cross-linking agent is 0.04-0.06%.

[0016] As a preferred embodiment of the method for preparing the slowly water-absorbing hydrogel for simulating a nerve compression model described in the present invention, the photoinitiator includes 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone; and the crosslinking agent includes N,N′-methylenebisacrylamide.

[0017] As a preferred solution of the method for preparing the slowly water-absorbing hydrogel for simulating a nerve compression model of the present invention, the mass fraction of chitosan hydrochloride in the SA-PAM-CSCL gel solution is 10-15%.

[0018] As a preferred embodiment of the method for preparing the slowly water-absorbing hydrogel for simulating a nerve compression model described in the present invention, the stirring comprises the following steps: the stirring speed is 150 to 200 rpm, the stirring temperature is 20 to 30° C., and the stirring time is 5 to 15 min.

[0019] As a preferred embodiment of the method for preparing the slowly water-absorbing hydrogel for simulating a nerve compression model of the present invention, the ultraviolet light irradiation time is 35 to 45 minutes.

[0020] Another object of the present invention is to overcome the deficiencies in the prior art and provide a slowly absorbing hydrogel.

[0021] The third object of the present invention is to overcome the deficiencies in the prior art and provide a slowly absorbing hydrogel for use in a model simulating nerve compression.

[0022] Beneficial effects of the present invention:

[0023] The present invention creatively prepares an interpenetrating network composite hydrogel through chemical crosslinking and physical crosslinking by electrostatic action. The method is simple to operate, and the prepared hydrogel has excellent slow water absorption performance: the swelling equilibrium time is not less than 90 hours, and the equilibrium swelling rate is not less than 300%; the compression performance is excellent: the compressive strength is not less than 20MPa, the compression modulus is not less than 20MPa, and the five compression cycle curves are basically overlapped. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:

[0025] Figure 1 (A) to (E) are unswollen comparative example 1 and examples 1 to 4; Figure 1 (a) to (e) are swollen Comparative Example 1 and Examples 1 to 4.

[0026] Figure 2 It is a line graph showing the change in swelling rate and equilibrium swelling rate of the composite hydrogels of Comparative Example 1 and Examples 1 to 4.

[0027] Figure 3 It is a bar graph of the swelling equilibrium time of the composite hydrogels of Comparative Example 1 and Examples 1 to 4.

[0028] Figure 4 (a) to (e) are five-cycle compression curves of Comparative Example 1 and Examples 1 to 4 at 80% strain. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0032] The raw materials used in the present invention are all commercially available unless otherwise specified.

[0033] The abbreviations of the substances in the present invention are as follows:

[0034] Sodium alginate (SA), acrylamide (AM), polyacrylamide (PAM), chitosan hydrochloride (CSCL), 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone (I2959), and N,N′-methylenebisacrylamide (MBA).

[0035] The raw materials and specifications used in the embodiments of the present invention are shown in the following table:

[0036]

[0037]

[0038] The performance of the material prepared in the embodiment of the present invention was tested as follows:

[0039] Scanning electron microscopy (SEM): The prepared hydrogels were divided into groups, one group was pre-frozen directly, and the other group was pre-frozen after swelling for 2 hours. Both groups were freeze-dried, and the dried specimens were quenched with liquid nitrogen. The morphological characteristics were recorded by SEM. The gold was sprayed evenly with an acceleration voltage of 3.0 kV.

[0040] Swelling performance test: The prepared hydrogel was placed at room temperature for 3 h and weighed to obtain the initial weight W. 0 The hydrogel sample was immersed in phosphate buffered saline (PBS) at room temperature and swollen. The hydrogel was taken out every 5 hours, the residual liquid on the surface was sucked off, and the sample was weighed to obtain the wet weight of the hydrogel sample W. s ; Repeat this process until the mass of the hydrogel no longer changes, that is, the swelling equilibrium is reached, and the swelling curve is obtained. The swelling behavior of the hydrogel in PBS buffer solution is studied to analyze the influence of the chemical composition and three-dimensional network structure of the hydrogel on its performance. The swelling rate (S%) of the hydrogel sample can be obtained by the following formula:

[0041]

[0042] Among them, W S W is the mass of the hydrogel when it swells at 25°C; 0 is the mass of the dry gel.

[0043] Compression cycle performance test: The compression cycle performance of the hydrogels was evaluated using a computerized tension-compression tester (KJ-1065A, Dongguan, China). The compression test of the hydrogels was performed at room temperature with a compression speed of 5 mm / min. The stress-strain curves were obtained using cylindrical hydrogels with a diameter of 12 mm and a height of 10 mm, and each test was repeated 5 times.

[0044] Example 1

[0045] This embodiment provides a method for preparing a slowly water-absorbing hydrogel for simulating a nerve compression model, specifically:

[0046] 1) Preparation of solution A: Add 2.63 g of chitosan hydrochloride to 50 mL of deionized water, stir at 25° C. for 50 min to mix well, and obtain a chitosan hydrochloride solution with a mass fraction of 5%, which is referred to as solution A;

[0047] 2) Preparation of solution B: 6.025 g acrylamide (AM) and 0.975 g sodium alginate (SA) were mixed with 43 ml deionized water to obtain an acrylamide-sodium alginate solution, referred to as solution B, wherein the mass fraction of acrylamide was 12.05% and the mass fraction of sodium alginate was 1.95%;

[0048] 3) Preparation of solution C: Add 0.04 g of photoinitiator 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone (I2959) and 0.0025 g of crosslinker N,N′-methylenebisacrylamide (MBA) to 5 g of solution B and mix well to obtain a SA-PAM solution, which is recorded as solution C;

[0049] 4) Add 0.26 g of solution A to 5 g of solution C to obtain a SA-PAM-CSCL gel solution, in which the mass fraction of CSCL is 5%, and let it stand to remove bubbles in the gel solution; then pour the gel solution into a culture dish and irradiate it with 365 nm ultraviolet light for 40 minutes to obtain a SA-PAM-CSCL 5% hydrogel.

[0050] Example 2

[0051] The difference between this embodiment and embodiment 1 is that the addition amount of solution A in step 4) is adjusted to 0.56 g, so that the mass fraction of CSCL in the SA-PAM-CSCL gel solution is 10%, and the rest of the preparation process is the same as that in embodiment 1 to obtain SA-PAM-CSCL 10% hydrogel.

[0052] Example 3

[0053] The difference between this embodiment and embodiment 1 is that the addition amount of solution A in step 4) is adjusted to 0.88 g, so that the mass fraction of CSCL in the SA-PAM-CSCL gel solution is 15%, and the rest of the preparation process is the same as that in embodiment 1 to obtain SA-PAM-CSCL15% hydrogel.

[0054] Example 4

[0055] The difference between this embodiment and embodiment 1 is that the addition amount of solution A in step 4) is adjusted to 1.25 g, so that the mass fraction of CSCL in the SA-PAM-CSCL gel solution is 20%, and the rest of the preparation process is the same as that in embodiment 1 to obtain SA-PAM-CSCL 20% hydrogel.

[0056] Comparative Example 1

[0057] The difference between this comparative example and Example 1 is that the amount of solution A added in step 4) is adjusted to 0, and the rest of the preparation process is the same as that in Example 1 to prepare SA-PAM hydrogel.

[0058] The hydrogels prepared in the above examples and comparative examples were characterized by microstructure. Figure 1 shown.

[0059] Figure 1 (A) to (E) are comparative example 1 and examples 1 to 4 that were not swollen, respectively; Figure 1 (a) to (e) are respectively Comparative Example 1 and Examples 1 to 4 which have been swollen. Figure 1 (A) It can be seen that the surface morphology of comparative example 1 is honeycomb-like, indicating that the network structure constructed by SA and PAM is distributed in an orderly manner. Figure 1 (B) to (E) It can be seen that after adding CSCL, the internal structure of the composite hydrogels of Examples 1 to 4 also has a similar typical honeycomb shape, but compared with the comparative example, the pores are relatively smaller and the pore distribution is more uniform. This is mainly because after CSCL is added to the composite hydrogel of SA and PAM, a more uniform and dense interpenetrating structure is formed between the three, which makes the pore size smaller. Figure 1 From the pore distribution of (B) to (E), it can be seen that the pore size of the hydrogel decreases with the increase of CSCL content; the pore thickness increases with the increase of CSCL content; the pore distribution becomes averaged with the increase of CSCL content, but when the CSCL content reaches 15%, the pore distribution decreases with the increase of CSCL content, indicating that excessive CSCL content will destroy the regularity of the cross-linked network due to the steric effect. Figure 1 From (b) to (e), it can be seen that the pores of the hydrogel after swelling become larger than those of the hydrogel before swelling due to water absorption, and the pore size of the hydrogel decreases with the increase of CSCL content.

[0060] The swelling performance of the hydrogels prepared in the above examples and comparative examples was tested, and the results are shown in Table 1 below.

[0061] Table 1

[0062]

[0063] Figure 2 The effect of different CSCL contents on the swelling rate change and equilibrium swelling rate of composite hydrogels; Figure 3 is the swelling equilibrium time of composite hydrogels with different CSCL contents.

[0064] From Table 1 and Figure 2 It can be seen that the swelling rate of comparative example 1 is very fast and the equilibrium swelling ratio is large, but the swelling equilibrium time is short, which is 32h. The swelling equilibrium time of embodiments 1 to 4 is higher than that of comparative example 1. This is because CSCL will form hydrogen bonds with the SA-PAM cross-linked network, making the system structure more stable and not easily destroyed by swelling. The swelling performance of embodiment 3 is the best, with a swelling equilibrium time of 116h and a equilibrium swelling ratio of 324.90%; the swelling equilibrium time of embodiment 1 is 39h, and the equilibrium swelling ratio is 328.89%; the swelling equilibrium time of embodiment 2 is 54h, and the equilibrium swelling ratio is 298.12%; the swelling equilibrium time of embodiment 4 is 106h, and the equilibrium swelling ratio is 386.98%. The swelling equilibrium time is shorter than that of embodiment 3. This is because excessive CSCL content will destroy the regularity of the cross-linked network due to the steric effect, making the gel structure unstable, thereby affecting the swelling performance. Figure 3 It can be seen that when the CSCL content is below 15%, increasing the CSCL content can significantly increase the swelling equilibrium time of the hydrogel. However, when the CSCL content is greater than 15%, with the increase of the CSCL content, the swelling rate change trend gradually increases, and the equilibrium swelling rate also increases, but the swelling equilibrium time is shortened. This is consistent with the results of microstructural characterization, indicating that the swelling equilibrium time is related to the pore size and porosity. As the pore size becomes smaller and the pore distribution becomes more uniform, the swelling equilibrium time becomes longer. However, when the CSCL content is too high, the regularity of the cross-linked network will be destroyed due to the steric effect, and the swelling equilibrium time will also decrease accordingly.

[0065] The hydrogels prepared in Comparative Example 1 and Examples 1 to 4 were subjected to compression performance tests.

[0066] Figure 4 (a) to (e) are five-cycle compression curves of Comparative Example 1 and Examples 1 to 4 at 80% strain. Figure 4It can be seen that during the cycle, the stress-strain curves clearly show different paths, giving hysteresis loops. Hysteresis loops are observed for all consecutive cycles. The hysteresis of the stress-strain curves throughout the process reflects the energy dissipation and viscoelasticity of the composite hydrogel. Figure 4 (a) It can be seen that the hysteresis loop area of ​​the first cycle of the comparative example is larger, and the hysteresis loop area of ​​the subsequent cycles becomes smaller, and the stress also gradually decreases, indicating that the energy is dissipated, and the quintic curves have almost no overlap, indicating that the comparative example has irreversible deformation. Figure 4 (b) to (e) it can be seen that the hysteresis loops of Examples 1 to 4 are all smaller, and Figure 4 (d) It can be seen that the five cycle curves of Example 3 are almost overlapped, and the macroscopic structure of the gel is not damaged at 80% strain, which shows that Example 3 not only exhibits good elastic properties, but also has very excellent self-recovery properties. This shows that the amide bonds in the network can maintain the integrity of the hydrogel, and at the same time, the presence of weak hydrogen bonds also helps dissipate energy during loading. However, when the CSCL content is too high (content 20%), Figure 4 (e) It can be seen that Example 4 will destroy the regularity of the cross-linked network due to the steric effect, and the overlap rate of the cycle curves is reduced, indicating that the self-healing performance is reduced.

[0067] Example 5

[0068] The difference between this embodiment and Example 3 is that the mass of the photoinitiator 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone (I2959) is adjusted from 0.04 g (mass fraction 0.8%) to 0.035 g (mass fraction 0.7%), and the rest of the preparation process is the same as that of Example 3 to obtain SA-PAM-CSCL hydrogel.

[0069] Example 6

[0070] The difference between this embodiment and Example 3 is that the mass of the photoinitiator 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone (I2959) is adjusted from 0.04 g (mass fraction 0.8%) to 0.0375 g (mass fraction 0.75%), and the rest of the preparation process is the same as that in Example 3 to obtain SA-PAM-CSCL hydrogel.

[0071] Comparative Example 2

[0072] The difference between this comparative example and Example 3 is that the photoinitiator 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone (I2959) is adjusted from 0.04 g (mass fraction 0.8%) to 0.045 g (mass fraction 0.9%), and the rest of the preparation process is the same as Example 1 to obtain SA-PAM-CSCL hydrogel.

[0073] The swelling performance test of the material prepared in the above embodiment was carried out, and the comparison results with those of embodiment 3 are shown in Table 2.

[0074] Table 2

[0075]

[0076] It can be seen from the above table that adjusting the amount of photoinitiator I2959 added has a significant effect on the performance of SA-PAM-CSCL hydrogel. When the content of the photoinitiator is lower than 0.8%, the swelling equilibrium time gradually increases with the increase of the initiator, and the equilibrium swelling rate gradually decreases. This is because the increase in free radicals makes the polymerization reaction and cross-linking reaction more complete, making the pore size of the composite hydrogel smaller, so that the water absorption is slow, meeting the requirement of slow water absorption. When the photoinitiator content is higher than 0.8%, the absorption rate is significantly reduced. The possible reason is that the increase in the concentration of free radicals causes the chain transfer reaction to cause excessive cross-linking between molecular chains, and the absorption rate decreases instead. In summary, the preferred mass fraction of the photoinitiator I2959 in the present invention is 0.8%.

[0077] Example 7

[0078] The difference between this embodiment and embodiment 3 is that the ultraviolet light irradiation time is adjusted from 40 min to 35 min, and the rest of the preparation process is the same as that of embodiment 1 to prepare SA-PAM-CSCL hydrogel.

[0079] Example 8

[0080] The difference between this embodiment and embodiment 3 is that the ultraviolet light irradiation time of 40 min is adjusted to 45 min, and the rest of the preparation process is the same as that of embodiment 1 to prepare SA-PAM-CSCL hydrogel.

[0081] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 3 are shown in Table 3.

[0082] Table 3

[0083]

[0084] As can be seen from the table above, adjusting the UV irradiation time has a significant effect on the performance of SA-PAM-CSCL hydrogels. This is because as the irradiation time shortens, the chain initiation and chain growth rates are affected, resulting in a decrease in the degree of polymerization and crosslinking, and gelation cannot be achieved; and when the irradiation time is too long, the crosslinked network formed is too dense, which will cause the hydrogel pore size to be too dense, rapidly absorb water and swell, and reduce the swelling equilibrium time. In summary, the preferred UV irradiation time of the present invention is 40 minutes.

[0085] Comparative Example 3

[0086] The 10wt% polyvinyl alcohol aqueous solution was subjected to three directional freeze-thaws using liquid nitrogen. The prepared hydrogel was immersed in an aqueous solution containing acrylamide (3.0mol / L), and after sufficient swelling, 60Coγ-ray radiation was used to initiate the polymerization of acrylamide, thereby forming a second network. The dried double-network structure hydrogel was immersed in a 10wt% glutaraldehyde aqueous solution for 30s, and dried immediately after immersion, and repeated ten times.

[0087] Comparative Example 4

[0088] The difference between this comparative example and Example 3 is that CSCL is adjusted to HACC (chitosan quaternary ammonium salt) and the rest of the preparation process is the same as Example 1 to prepare SA-PAM-HACC hydrogel.

[0089] The performance of the material obtained in the above comparative example was tested, and the comparison results with those of Example 3 are shown in Table 3.

[0090] Table 3

[0091]

[0092] As can be seen from the above table, Comparative Example 3 is a hydrogel currently used to simulate the nerve compression model, and its swelling equilibrium time is very short, which cannot meet the requirements of the animal model of simulating chronic nerve compression; the addition of HACC in Comparative Example 4 leads to obvious entanglement of the hydrogel macromolecular chains, thereby affecting the swelling behavior of the hydrogel. - The existence of ions balances the charge and avoids excessive entanglement of macromolecules.

[0093] Through the above examples and comparative examples, it is found that after five compression cycles of Examples 1 to 4, the hysteresis loops all become smaller, and the five-cycle curves of Example 3 are almost overlapped, and the macroscopic structure of the gel is not damaged at 80% strain, which shows that Example 3 not only exhibits good elastic properties, but also has very excellent self-recovery properties. It is confirmed that Example 3 has an excellent effect in improving the compression resistance of the hydrogel by combining CSCL in the SA-PAM system through a specific method.

[0094] In summary, the present invention creatively prepares an interpenetrating network composite hydrogel through chemical crosslinking and physical crosslinking by electrostatic action. First, a chitosan hydrochloride (CSCL) aqueous solution of a specific concentration is prepared for use, and then acrylamide (AM) and sodium alginate (SA) solutions of a specific ratio are prepared, and then a photoinitiator (I2959) and a crosslinker (N, N′-methylenebisacrylamide) of a specific ratio are added and mixed evenly, and then a certain ratio of chitosan hydrochloride (CSCL) solution is added, and finally the solution is transferred to a culture dish, and irradiated with 365nm ultraviolet light for 35 to 45 minutes at room temperature to obtain SA-PAM-CSCL hydrogel.

[0095] Acrylamide (AM) and crosslinker N,N′-methylenebisacrylamide (MBA) were used together with photoinitiator 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone (I2959) to prepare PAM network through free radical polymerization to obtain the basic hydrogel skeleton. Sodium alginate (SA), as a natural anionic polysaccharide, can be crosslinked with divalent or multivalent cations to form hydrogels. It has attracted much attention due to its abundant sources and low price. Chitosan hydrochloride (CSCL), as a chitosan derivative, has attracted much attention due to its solubility and antibacterial properties. As one of the hot research directions in the field of modified chitosan, the use of salt to modify chitosan not only retains the advantages of chitosan itself, but also further enhances the positive charge and bactericidal and antibacterial effects. Due to the -NH 2 The -COOH in the SA molecule can be chemically cross-linked to form an amide bond, thereby constructing a new network structure. SA and CSCL interact electrostatically to form an interpenetrating network structure between macromolecules, increasing the porosity and cross-linking density of the hydrogel, and achieving a balance between slow water absorption and compression performance. This solves the problem of rapid water absorption and structural instability of traditional hydrogels.

[0096] The present invention has found that when the first layer network system is prepared by chemical crosslinking, the ratio of acrylamide to sodium alginate, the mass fraction of a photoinitiator and a crosslinker will affect the morphology of the composite hydrogel and its stability in aqueous solution; the study found that when the mass fraction of acrylamide in the acrylamide and sodium alginate aqueous solution is 12.0-12.5%, the mass fraction of sodium alginate is 1.5-2.0%, the mass fraction of the photoinitiator I2959 in the polyacrylamide-sodium alginate aqueous solution is 0.7-0.8%, and the mass fraction of the crosslinker MBA is 0.04-0.06%, obvious macromolecular agglomeration can be avoided and a balance between good slow water absorption performance and high compression resistance can be achieved simultaneously.

[0097] The present invention has found that in the process of preparing polyacrylamide-sodium alginate-chitosan hydrochloride composite hydrogel based on the polyacrylamide-sodium alginate solution under the above-mentioned optimized conditions, the slow water absorption performance and compression resistance of the hydrogel are significantly improved when the mass fraction of chitosan hydrochloride in the mixed system is 10-15%, and the concentration and solid content of the chitosan hydrochloride aqueous solution are 4.8-5.2wt%. When a 15% by mass CSCL solution is added to the SA-PAM solution, a SA-PAM-CSCL composite hydrogel is obtained, which can simultaneously achieve the following properties: (1) excellent slow water absorption performance: the swelling equilibrium time is not less than 90h, and the equilibrium swelling rate is not less than 300%; (2) excellent compression performance: the compressive strength is not less than 20MPa, the compression modulus is not less than 20MPa, and the five compression cycle curves are basically overlapped.

[0098] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a slowly water-absorbing hydrogel for simulating a nerve compression model, characterized in that: include, Chitosan hydrochloride and deionized water are mixed to obtain solution A; Acrylamide and sodium alginate are mixed evenly with deionized water to obtain solution B; Add photoinitiator and crosslinking agent into solution B and mix evenly to obtain solution C; Solution C and solution A were stirred into a uniform solution to obtain a SA-PAM-CSCL gel solution, which was then irradiated with 365 nm ultraviolet light to obtain a SA-PAM-CSCL hydrogel.

2. The method for preparing the slowly water-absorbing hydrogel for simulating a nerve compression model according to claim 1, characterized in that: The mass fraction of chitosan hydrochloride in the solution A is 4.8-5.2%.

3. The method for preparing the slowly water-absorbing hydrogel for simulating a nerve compression model according to claim 1, characterized in that: In the solution B, the mass fraction of acrylamide is 12.0-12.5%, and the mass fraction of sodium alginate is 1.8-2%.

4. The method for preparing the slowly water-absorbing hydrogel for simulating a nerve compression model according to claim 1, characterized in that: In the solution C, the mass fraction of the photoinitiator is 0.7-0.8%, and the mass fraction of the cross-linking agent is 0.04-0.06%.

5. The method for preparing the slowly water-absorbing hydrogel for simulating a nerve compression model according to claim 4, characterized in that: The photoinitiator includes 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone; and the crosslinking agent includes N,N′-methylenebisacrylamide.

6. The method for preparing the slowly water-absorbing hydrogel for simulating a nerve compression model according to claim 1, characterized in that: The mass fraction of chitosan hydrochloride in the SA-PAM-CSCL gel solution is 10-15%.

7. The method for preparing the slowly water-absorbing hydrogel for simulating a nerve compression model according to claim 1, characterized in that: The stirring has a stirring speed of 150 to 200 rpm, a stirring temperature of 20 to 30° C., and a stirring time of 5 to 15 min.

8. The method for preparing the slowly water-absorbing hydrogel for simulating a nerve compression model according to claim 1, characterized in that: The ultraviolet light irradiation time is 35 to 45 minutes.

9. A slowly water-absorbing hydrogel prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the slowly water-absorbing hydrogel according to claim 9 in a simulated nerve compression model.

Citation Information

Patent Citations

  • High-strength chemical-physical dual-network hydrogel with self-recovery capability, and preparation method and application of hydrogel

    CN107011609A

  • Physical and chemical synergetic cross-linked high-strength hydrogel as well as preparation method and application thereof

    CN118703010A

  • Bio-inspired degradable tough adhesives for diverse wet surfaces

    US20210338577A1

  • Hydrogel for ostomy appliances

    WO2024186960A1